1990
DOI: 10.1159/000248002
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Delayed Hypersensitivity Reaction Following a Sea Urchin Sting

Abstract: The case of a 28-year old woman with pruritic and erythematous eruptions on the knees and ankle about 10 days after being stung by sea urchin is reported. The spines of a sea urchin were ground, extracted and patch-tested, to which the patient showed a positive delayed skin reaction. Based on the clinical course and positive patch tests, it was concluded that the patient developed a delayed hypersensitivity reaction to the sea urchin’s stinger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This range of different forms has widened the spectrum of the hypotheses in regard to the actual nature of sea urchin granuloma, and the model of a mere foreign body reaction has been flanked by the one of an immune response against nonself organic material, suggested by the newly reported pictures. Such a model is also supported by the finding of spontaneous and experimentally induced, delayed hypersensitivity cutaneous reactions, with the clinical and histologic features of allergic contact dermatitis, in patients with sea urchin granuloma [6,7]. The inert substances responsible for the foreign body reaction are thought to be the inorganic constituents of the spines, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…This range of different forms has widened the spectrum of the hypotheses in regard to the actual nature of sea urchin granuloma, and the model of a mere foreign body reaction has been flanked by the one of an immune response against nonself organic material, suggested by the newly reported pictures. Such a model is also supported by the finding of spontaneous and experimentally induced, delayed hypersensitivity cutaneous reactions, with the clinical and histologic features of allergic contact dermatitis, in patients with sea urchin granuloma [6,7]. The inert substances responsible for the foreign body reaction are thought to be the inorganic constituents of the spines, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…1 The pathogenesis remains uncertain, and sea urchin granuloma was considered a foreign body reaction or an unusual immunologic response to an as yet unidentified antigen. 2,12 Although it is unknown whether calcium carbonate alone could produce such a reaction, this problem is unique to sea urchin spines. It is also suggested that Mycobacterium marinum may play a pathogenic role in some cases of sea urchin granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…These injuries usually raise an immediate reaction characterized by local pain, burning, erythema, and edema that subside in a few hours if the spine fragments are completely removed. 1,2 In contrast, a remnant of the spine tip remaining in the wound frequently causes a delayed response, which is called sea urchin granuloma. 3 When joints are penetrated, the inflammation may take on the form of a florid granulomatous synovitis, which can result in joint destruction (sea urchin spine arthritis) if appropriate therapy is not provided in time.…”
mentioning
confidence: 99%
“…could be the agent responsible for sensitization. Usually no microorganisms, sarcoidal diathesis or metals likely to produce granulomas have been detected; the spine silica content is about 0·55%, but no polarized material has been identified in biopsies 5,6 , 12 . The first description 13 suggested papulonecrotic tuberculide, and although a mycobacterial infection was sought, 7 acid‐fast bacilli were detected in only one case 14 in which the authors proposed that echinoderm granuloma could be a new mycobacterial infection.…”
Section: Discussionmentioning
confidence: 99%